COMMERCIAL ISSUES IN ISLAMIC SPIRITUALITY - Tojiboev Abdug’ani Abdumalikovich (American Journals, 2023)
The article describes the rules of commerce, trade, and law in Islam. Local Market, Regional Market, National Market and World Market are mentioned which show the prestige and glory of the cities.
Keywords: Shariah, deposit, halal, usurer, hadith, commercial, measure, state, adult, quantity, amount, added value.